Machado da. Mercúrio total em parturientes e neonatos da Cidade de Itaituba-Pará-Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
Introduction: Due to the natural and anthropogenic processes, nowadays Mercury (Hg) is one of the main contaminants of soils and rivers of the Tapajós River region. This metal exists in nature in metallic, inorganic and organic forms, being this last one the one of greater concern at the level of the human toxicity. The environmental exposure to Hg via the food chain, mainly for consumers of higher trophic level, including humans, is significantly higher, once this metal presents high toxicity and capacity to undergo bioaccumulation and biomagnification along the food chains, by the ingestion of food (fish, crustaceans and cephalopods). Objective: To determine the levels of total mercury (HgT) in populations of neonates and their mothers. Methodology: Consists of an observational, quantitative, analytical and exploratory investigation, carried out through bibliographic, field and laboratory research, using biological matrices of hair and nail samples (maternal), umbilical cord tissue and umbilical cord blood (neonates), research at the Obstetrics Clinic of the Municipal Hospital of Itaituba - Pará, with the approval of CEP/UEPA under seem: 3.031.069, with 110 voluntary parturients, after signing the Free and Informed Consent Term, and application of a semi-structured questionnaire. Results and discussion. The concentration of THg being the mean ± standard deviation found: in hair was (1 ,83 ± 2,48), in nail (0,72 ± 0,91), and in umbilical cord blood (0,07 ± 0,14) µg/g and in cord blood (0,005 ± 0,005) µg/L. The concentrations presented are within the values considered safe and do not present neurological alterations in the mother or risk for neonates according to the reference values of the World Health Organization. Conclusion: The toxic effects of Hg are determined by the amount of metal involved and the time of exposure. Fetal neurotoxicity and post-natal changes, such as developmental delay or other neurological changes, may occur in the children of women exposed to Hg during pregnancy. Thus, the continuous monitoring of the presence of this metal in humans and the environment makes it essential, in order to avoid the occurrence of human contamination by Hg.
Keywords: Gestantes; Cordão Umbilical; Cabelo; Amazônia; CNPQ::CIÊNCIAS DA SAÚDE::FARMÁCIA::TECNOLOGIA FARMACÊUTICA; Fisiologia ambiental